Analysis of Logistics Risk Management at the Shipping Company PT XYZ Tbk. in North Jakarta Using the ISO 31000:2018 Risk Management Analysis Framework - Karya Bakti Kaban (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The logistics industry plays a strategic role in supporting the smooth functioning of the national supply chain; however, it faces various risks that can impact operational effectiveness, service quality, and business continuity. As a logistics and shipping service provider in Indonesia, PT XYZ Tbk. encounters potential risks such as delivery delays, cargo damage, port operational disruptions, IT system failures, workplace accidents, and external factors like extreme weather and regulatory changes. This study aims to identify, analyze, and evaluate the logistics risks faced by PT XYZ Tbk. and to provide recommendations for risk treatment, guided by the ISO 31000:2018 standard. The research employs a qualitative descriptive method using a case study approach. Data were gathered through observation, interviews, documentation, and a literature review. The risk analysis process involved establishing the context, identifying risks, analyzing risks based on likelihood and impact, evaluating risks using a risk matrix, and formulating risk treatment recommendations in accordance with ISO 31000:2018 principles. Based on the analysis using the ISO 31000 approach and a risk matrix, it is concluded that PT XYZ Tbk. faces various risks in its logistics operations. The highest-rated risks include adverse weather, vessel delays, and port congestion. These risks significantly impact the smooth distribution of goods, operational costs, and customer satisfaction. Implementing structured risk management can assist the company in more effectively identifying, analyzing, evaluating, and controlling risks. Consequently, the company can enhance its operational resilience and competitiveness within the maritime logistics industry. Recommended risk treatment strategies include logistics digitalization via IoT and GPS tracking, the use of Artificial Intelligence (AI) to assist in predicting potential delays, the implementation of an integrated risk dashboard, the development and implementation of a Business Continuity Plan (BCP), the strengthening of cybersecurity, personnel training programs, collaboration with ports and regulatory bodies, and the implementation of periodic risk monitoring and evaluation. This research is expected to contribute to PT XYZ Tbk. by enhancing the effectiveness of its logistics risk management and strengthening its operational resilience, while also serving as a reference for other logistics companies implementing ISO 31000:2018 as a risk management framework.